Referential fallacy: pragmatic conceptualization of Michael Riffaterre - Дударева, О. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
The article gives a historical analysis of the emergence of the idea of referential illusion in literary theory. The object of study is described in the context of previous concepts of the theory of literature, such as «intentional fallacy» and «affective fallacy» that allows to compare them and to identify the main differences. Philosophical and anthropological analysis of the concept of “referential illusion” can demonstrate the effectiveness of avoiding criticism for attempting realizing the function and necessity of such phenomena in the literary experience.